The Alterations in Peripheral Blood Components of Women with Abnormal Cervical Cytology - Mine Kiseli; Aslı Yarcı Gürsoy; Egemen Akıncıoğlu; Emre Göksan Pabuçcu; Gamze Sinem Çağlar; Hande Esra Koca; Zehra Edebal; Haldun Umudum (Medical Network, 2016)
OBJECTIVE: To investigate the peripheral blood components, neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratios (PLR) in cervical cytological abnormalities. STUDY DESIGN: We retrospectively analyzed 185 cases with abnormal and 303 cases with normal cervicovaginal smears (CVS) with blood count profile, from a total number of 9286 patients. RESULTS: Abnormal CVS results consisted of 137 (72%) ASC-US, 16 (8%) ASC-H, 19 (10%) L-SIL, 4 (2%) H-SIL and 9 (4%) AGUS. NLR and PLR of abnormal CVS group were higher than control group (p<0.001). The lymphocyte count was significantly lower in abnormal CVS cases (p<0.001). The number of patients with neutrophilia (neutrophils ≥70% of the total leukocytes) was similar among two groups (p>0.05). CONCLUSION: Neutrophilia is not observed in cervical preinvasive lesions whereas it is common in cervical cancer. In this study, absence of increased neutrophil counts and presence of lymphopenia in patients with abnormal cervical cytology, may indicate an early measure in cervical pathologies.